The effect a Bridge Resource Management course has upon the attitude towards Non-Technical Skills - Sondell, Jessica; Lyman, Matilda (My University, 2020)
The concept of Bridge Resource Management has been a part of the maritime industry since 1992 and in 2011 it became a part of international regulations for bridge officers to obtain training in BRM. The motive was to decrease accidents and strengthen safety at sea by educating officers to become more aware and learn how to exploit their NTS; as they are considered to be as important as one’s technical proficiency. It is proven that NTS do make people more efficient and act safer. This study was executed to see if it was possible to establish a correlation between bridge officer’s attitude towards NTS before and after a BRM course was attended. A quantitative method was used as the participants received an online questionnaire before and after attending a BRM course at Chalmers. The responses were given on a scale from 1 to 5 i.e. a Likert scale, providing data on their attitude; how much they agreed with the statements given. The questionnaires’ results were analyzed and compared using Microsoft® Excel® to establish if a change of attitude had occurred as a result of attending the BRM course. The results show no significant difference between the responses before and after the course, meaning the officers’ attitude towards NTS did not significantly improve after attending the three-day BRM course. This does not, however, indicate that the BRM course was unnecessary. The results together with previous research show that the officers in this study had a good attitude towards NTS to begin with. The officers’ perception of the training was that they did gain knowledge and as BRM is still evolving to fit the needs of the maritime industry its importance as a safety course should not be discarded. Conclusively, this subject needs more research to evaluate and determine what could be done to develop BRM training to make it a better fit for the maritime industry.
Keywords: NTS; BRM; MRM; Attitude; Maritime Industry; ROPAX; Bridge Officers